Pengaruh Minat Baca Mahasiswa Terhadap Hasil Belajar Pada Mahasiswa Jurusan Bimbingan Konseling Islam IAI Darussalam Blokagung - M. Rizqon Al Musafiri (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Interest reading is only part of the variable that affects the learning outcomes achieved by students. This study aims to determine the effect of reading interest on student learning outcomes BKI at the Institute of Islamic Religion Darussalam Blokagung. This research is an exposed facto research that is correlational. The population in this study are all students of Islamic Institute of Darussalam Blokagung force of 2016. Students who have followed the philosophy courses in the odd semester of 2016 amounted to 33 students. Data collection techniques consist of questionnaires and documentation. The result of partial correlation analysis between reading interest variable (X) and learning result variable (Y) shows that the value of R calculated at 0.440, which was higher than the R-table is 0.297 with a significant value of 0.05. This indicates that the Rarithmetic>Rtable; sig <Î± of 0.05 (0.440> 0.297; 0.00 <0.05). Thus, it can be said that interest in reading students have a positive and significant effect on student learning outcomes.